Pengaruh Kepemimpinan, Kompensasi, Komunikasi, dan Motivasi Kerja terhadap Turnover Intention Pegawai dengan Kepuasan Kerja sebagai “Variabel Antara” - Siti Noor Hidayati; Suryadi Dwi Saputra (Jurnal Maksipreneur, 2018)
Leadership, compensation, communication, and work motivation positively affect the job satisfaction. Otherwise, job satisfaction negatively affect turnover intention. The results of 83 respondents of FTI UPN Veteran Yogyakarta employees can be explained as follows, it is proved significanly that there is an indirect influence of leadership, compensation, communication, and work motivation to turnover intention with job satisfaction as intermediate variable. While the direct effect of those variables are not significant. Between the four independent variables, the most dominant influence to increase job satisfaction and subsequently lower turnover intention is the work motivation.